IMPLEMENTASI BUDAYA MEMBACA YAASIIN BERSAMA SEBELUM PEMBELAJARAN DI MADRASAH ALIYAH MAMBAUL ULUM COROGO JOMBANG - Fadhilah, Alfin; Jumari (PAI FAI UNHASY Tebuireng Jombang, 2023)
This article intends to describe how the implementation of the yaasiin reading culture before learning, knowing the planning of the yaasiin reading culture, knowing the implementation of the yaasiin reading culture, knowing the evaluation system for the yaasiin reading culture, and knowing the inhibiting factors and their solutions as well as the results of implementing the yaasiin reading culture before learning. This research includes qualitative research. There are two sources of data, namely primary data sources and secondary data sources. The data were obtained using observation, interview and documentation techniques. Data analysis was carried out with the method of compiling, connecting, reducing, presenting, then the data could be concluded. The results of this study revealed three findings, namely the implementation of the Yaasiin reading culture before learning at MA Mambaul Ulum Corogo including planning, implementing and evaluating the Yaasiin reading culture before learning. Implementation of the Culture of Reading Yaasiin Together Before Learning at Madrasah Aliyah Mambaul Ulum Corogo runs conducive, and istiqomah